Implementasi Program Jaminan Kesehatan (JKN) Dalam Presfektif Pelayanan Publik Di RSUD Dr Doris Sylvanus Palangka Raya - Milka Milka (Pencerah Publik, 2018)
This study aims to: find out and analyze the implementation of the Health Insurance Program (JKN) in the perspective of public services at the Regional General Hospital, dr. Doris Sylvanus Palangka Raya. The method used in this research is qualitative with qualitative descriptive type. Observation data collection techniques, interviews and documentation, Observation test uses the Standard Operating Procedure of the National Health Insurance Program (JKN) and uses the Principles and Principles of Public Service. The results show that 1). There needs to be improved services both in terms of administrative services, direct health services, and the need for additional human resources, accompanied by facilities and infrastructure. 2). Need to establish intensive communication between the Health Social Security Administration Agency, and the Regional General Hospital dr. Doris Sylvanus Palangka Raya, related to service delivery, service delivery and health service flow. As well as information related to the implementation of the JKN program at the Regional General Hospital, dr. Doris Sylvanus Palangka Raya. Recommendations 1. There is a need to improve services both in terms of administrative services, health services directly, and the addition of human resources, accompanied by facilities and infrastructure. 2. It is necessary to establish intensive communication between the Health Social Security Administration Agency, and the Regional General Hospital, dr. Doris Sylvanus Palangka Raya, related to service delivery, service delivery and health service flow. 3. There needs to be support from the central and regional governments both legislative and executive in allocating budgets in improving facilities and markets.